Exploring the potential of sprouted soybean and sesame hull to increase nutritional value of ice cream - A. A. A. El-Maksoud; M. A. Hesarinejad; T. G. Abedelmaksoud (Пищевые системы)
The study aimed to produce nutritionally enhanced ice cream by adding sprouted soybean (SSB) and sesame hulls (SH) at different concentrations to partially replace skimmed milk powder (SMP). The physicochemical, total phenolic content (TPC), antioxidant activity (AOA), and sensory acceptability of ice cream fortified with SSB or SH were evaluated. The ice cream containing 15% SSB was found to have the best sensory characteristics and was most preferred by the taste panel. The addition of 15% SSB increased the protein and fiber content and improved melting resistance, while the addition of 15% SH resulted in a greater increase in dietary fiber but lower protein content and melting resistance. The highest overrun on the cost was obtained in the sample fortified with 25% SSB compared to the lowest in the sample fortified with 25% SH, but panelists generally did not like these samples in terms of taste-flavor. The study concluded that the addition of SSB and SH to replace SMP in ice cream can create a nutritious and low-cost product with similar physicochemical properties and acceptance to the control.